Combined treatment of acute purulent sinusitis - G. N. Izotova; N. L. Kunelskaya; A. F. Zakharova; A. A. Sedinkin; I. Popova (Медицинский совет, 2013)
Acute sinusitis is the most common condition in otorhinolaryngology [4]. Acute sinusitis adversely affects the quality of life and professional activity. Quite simple at first glance, the disease often leads to serious complications. Moreover, its treatment is associated with significant costs [5], making acute sinusitis one of the most relevant issues for otorhinolaryngology.